#### Answer

$(4x^2+1)(2x+1)(2x-1)$

#### Work Step by Step

The product of a binomial sum and a binomial difference is: $(A+B)(A-B)=A^2-B^2$.
Hence here: $16x^4-1=(4x^2)^2-1^2=(4x^2+1)(4x^2-1)=(4x^2+1)((2x)^2-1^2)=(4x^2+1)(2x+1)(2x-1)$

Published by
Pearson

ISBN 10:
0-13417-894-7

ISBN 13:
978-0-13417-894-3

$(4x^2+1)(2x+1)(2x-1)$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.